2-(x/3)=-2

Simple and best practice solution for 2-(x/3)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(x/3)=-2 equation:



2-(x/3)=-2
We move all terms to the left:
2-(x/3)-(-2)=0
We add all the numbers together, and all the variables
-(+x/3)+2-(-2)=0
We add all the numbers together, and all the variables
-(+x/3)+4=0
We get rid of parentheses
-x/3+4=0
We multiply all the terms by the denominator
-x+4*3=0
We add all the numbers together, and all the variables
-1x+12=0
We move all terms containing x to the left, all other terms to the right
-x=-12
x=-12/-1
x=+12

See similar equations:

| (x+14)(x+13)=15 | | X+9+x+9=3x+9 | | C=5c+10 | | -3-11c=-12c | | -38-5x=x+4 | | x+43=100 | | 6x+2+x=30 | | 6x-7/5=7 | | 3p=49 | | 2(x+7)-5x+3=5–7x | | -3=-(r-15) | | 15h+h+2=19+17h | | 20.50a+3.75(82)=2071.50 | | y=-(-10²)-10+13 | | -2(8n-8)-3(1n+n)-6(2-3n)=-1 | | 12/1=-4/3b | | 8(4y-11)+3y=19(6y+21)-91 | | 9x+(7x)=80 | | 5x+24+×+36=180 | | −60x+32=−60x−32−60x+32=−60x−32 | | 2x-2+x+13=180 | | -16d-17=-19d+19 | | 499=15x+200 | | 124-u=219 | | -4s+13=25 | | -6x-4+7x=-15 | | -r+2=-10+8r-5r | | 4.00x+1.00=3.75x+2.00 | | 3-5(x+7)=23 | | 2(4x-3)-10=4+2x | | 4x-4+6x-22=90 | | 4-8x+5)=-18x-36 |

Equations solver categories